2016
DOI: 10.1177/1367006916629222
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between the morphological knowledge and L2 online processing of derivational words

Abstract: Objectives/Research Questions: Two experiments were conducted to investigate the effect of morphological knowledge on second language (L2) online processing of derivational words by Chinese first language (L1)–English L2 learners. Methodology: Experiment 1 was performed at the single word level with a masked priming paradigm using the lexical decision task. Experiment 2 was conducted at the sentence level with a self-paced reading paradigm. According to their performance on the morphological knowledge test, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 48 publications
0
8
0
Order By: Relevance
“…Although few studies have compared advanced adult L2 learners from different L1 morphological types in their L2 morphological awareness, results from previous online morphological processing studies of advanced adult L2 learners have hinted at the probability of an effect of L1 morphological type on L2 morphological awareness. First, offline L2 morphological awareness has been shown to influence online L2 morphological processing in advanced adult L2 learners after controlling for language proficiency (Deng et al, 2016(Deng et al, , 2017. L2 learners with higher morphological awareness have a greater tendency to automatically decompose morphologically complex words online, similarly to native speakers (Deng et al, 2016(Deng et al, , 2017.…”
Section: Cross-linguistic Influence Of Morphological Awarenessmentioning
confidence: 99%
See 1 more Smart Citation
“…Although few studies have compared advanced adult L2 learners from different L1 morphological types in their L2 morphological awareness, results from previous online morphological processing studies of advanced adult L2 learners have hinted at the probability of an effect of L1 morphological type on L2 morphological awareness. First, offline L2 morphological awareness has been shown to influence online L2 morphological processing in advanced adult L2 learners after controlling for language proficiency (Deng et al, 2016(Deng et al, , 2017. L2 learners with higher morphological awareness have a greater tendency to automatically decompose morphologically complex words online, similarly to native speakers (Deng et al, 2016(Deng et al, , 2017.…”
Section: Cross-linguistic Influence Of Morphological Awarenessmentioning
confidence: 99%
“…First, offline L2 morphological awareness has been shown to influence online L2 morphological processing in advanced adult L2 learners after controlling for language proficiency (Deng et al, 2016(Deng et al, , 2017. L2 learners with higher morphological awareness have a greater tendency to automatically decompose morphologically complex words online, similarly to native speakers (Deng et al, 2016(Deng et al, , 2017. Deng et al suggested that L2 learners with higher morphological awareness might be more inclined to explicitly analyse morphologically complex words into separate morphemes during reading, which, with practice, could contribute to more native-like automatic online decomposition of morphologically complex words.…”
Section: Cross-linguistic Influence Of Morphological Awarenessmentioning
confidence: 99%
“…Often taking the form of masked priming tasks, numerous studies have revealed learner sensitivity to L2 morphology (Bosch et al 2017;Deng et al, 2016a;Rehak & Juffs, 2010). Critically, to date most of these L2 processing studies have focused on inflection, not derivation, as Deng et al (2016a) note. For example, in Rehak and Juffs (2010), participants with English, Spanish, and Chinese L1s ("advanced/proficient" L2 English) 1 completed lexical decision tasks in English involving words with derivational prefixes.…”
Section: Learner Language and Productivitymentioning
confidence: 99%
“…We highlight, however, two notable exceptions of studies that measure participants' morphological knowledge prior to conducting processing research. In Deng et al (2016a), the 40 Chinese-speaking learners of English were given a morphological knowledge test in which participants selected correct word forms. After controlling for overall language proficiency (B1 on the Common European Framework of Reference [CEFR] for both groups), it was found that greater priming occurred for the group with higher morphological knowledge, as well as slower reading times.…”
Section: Corpus Findingsmentioning
confidence: 99%
See 1 more Smart Citation